Structural packaging : design your own boxes and 3-D forms. - Jackson, Paul (London : Laurence King, 2012)
Unlike other packaging titles, which simply provide templates to copy, this book enables designers of all packaging types to create 3-D packaging forms that are specific to their needs rather than based on an existing design. It teaches a simple ‘net’ construction system – a one-piece 2-D configuration of card seen when a 3-D package is opened out and flattened – which enables the designer to create a huge number of very strong 3-D packaging forms that are both practical and imaginative. Each chapter concludes with photographs and net drawings of 6–10 creative examples of packaging designs made using the principles outlined in the preceding chapter. Structural Packaging gives the reader an understanding of the underlying principles of packaging construction and the technical knowledge and confidence to develop a greater number of their own unusual and innovative designs than any comparable book.
boek